Strengthen gender mainstreaming and social inclusion in innovation challenges: Recommendations - Chavarro Rodriguez, Monica; Vanegas Cubillos, Martha; Casallas Martinez, Ivon M; Yomayuza Herrera, Karoll Valentina (2024)
The Sustainable Cocoa Innovation Challenge: nancing scalable solutions for peace building and climate change mitigation, was held in Colombia between August and November 2023. The challenge sought to identify, accelerate and nance innovative start-ups within the cocoa value chain in the country to promote sustainable land use practices to mitigate climate change and foster peacebuilding. The challenge was carried out as a collaboration between the One CGIAR research initiatives AgriLAC Resiliente and Mitigate+ and the project "Implementing sustainable agricultural and livestock systems for simultaneous targeting of forest conservation for climate change mitigation (REDD+) and peacebuilding in Colombia", known as the IKI-SLUS project. Both initiatives and the project aim to contribute to the achievement of sustainable food systems by scaling sustainable land use practices. The Alliance Bioversity International and the Center for Tropical Agriculture (CIAT), CGIAR's Accelerate for Impact (A4IP) platform and the Rockstart accelerator powered the challenge, providing technical expertise and a network of contacts in Latin America to ensure that the cocoa industry contributes to forest conservation and peacebuilding. As part of the conclusion of the rst four years of AgriLAC Resiliente, Work Package 3, which focuses on developing agroforestry systems that meet mitigation and sustainable development goals, along with the gender team, reviewed the lessons learned from the development of the challenge. The goal was to generate recommendations on the inclusion of gender and social inclusion approaches in future challenges led by the Alliance Bioversity International and Center for Tropical Agriculture (CIAT).